Maturogenesis of Two Maxillary Central Incisors: A Case Report with 10 Years of Follow Up - Abdollah Ghorbanzadeh; Atiyeh Ghorbanzadeh (Tehran University of Medical Sciences, 2015)
This case report describes the treatment of two immature maxillary central incisors in a 7- year-old female patient. She suffered complicated crown fracture because of trauma, and the root formation was incomplete. White mineral trioxide aggregate (MTA) was selected as the pulp-capping material after cervical pulpotomy to preserve the pulp tissue vitality and achieve maturogenesis. Follow-up evaluations showed successful treatment in terms of preservation of pulp vitality and demonstrated marked continuous physiological root devel- opment. During 10 years of follow-up, both teeth were clinically asymptomatic, and radio- graphic evaluations showed apparent root regeneration with apical root-end closure without pulp or periapical pathosis.